Analisis Tipologi dan Komposisi Penduduk Kampung Tua Tanjung Riau Sekupang - I Gusti Ngurah Anom Gunawan; Carlos Willyam (Journal of Architectural Design and Development (JAD), 2021)
Batam City is very famous for its coastal settlement areas. One of them is Tanjung Riau. Tanjung Riau is the name of a sub-district located in Sekupang sub-district, Batam City, Riau Islands, Indonesia. The area of this kelurahan is 23.90 km², with a population in 2020 of 23,987 people and a density of 1,004 people / km². This old village is an area that is very useful as a visit destination if the systems and facilities are well managed.. Therefore, this research is based on the typology of buildings and population composition and the problems found will be sought so that they can provide solutions to problems in the research.